2011
DOI: 10.1111/j.1348-0421.2011.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-I: fungal biota analyses of the Japanese experimental module KIBO of the International Space Station before launch and after being in orbit for about 460 days

Abstract: In addition to the crew, microbes also find their way aboard the International Space Station (ISS). Therefore, microbial monitoring is necessary for the health and safety of the crew and for general maintenance of the facilities of this station. Samples were collected from three sites in the Japanese experimental module KIBO on the ISS (air diffuser, handrail, and surfaces) for analysis of fungal biota approximately 1 year after this module had docked with the ISS. Samples taken from KIBO before launch and fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…The abundance of bacteria in the ISS-Kibo was equivalent to or lower than that on the surfaces in our laboratory (10 5 cells/cm 2 ) 10) , and bacteria detected in the ISS-Kibo was related to the human skin microbiota. Furthermore, with regard to fungal biota analyses, Satoh et al reported that the degree of cleanliness in the ISS-Kibo during the first 460 days was equivalent to that in a conventional clean room environment on the ground 19) . Surfaces of equipment installed in the ISS-Kibo are usually wiped with disinfectant once a week.…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of bacteria in the ISS-Kibo was equivalent to or lower than that on the surfaces in our laboratory (10 5 cells/cm 2 ) 10) , and bacteria detected in the ISS-Kibo was related to the human skin microbiota. Furthermore, with regard to fungal biota analyses, Satoh et al reported that the degree of cleanliness in the ISS-Kibo during the first 460 days was equivalent to that in a conventional clean room environment on the ground 19) . Surfaces of equipment installed in the ISS-Kibo are usually wiped with disinfectant once a week.…”
Section: Resultsmentioning
confidence: 99%
“…Fungal diversity in cleanrooms and medical settings has primarily been addressed through culture-based methods and is known to feature a large proportion of fungi related to humans and human activities (5,11,21,30,48,55). However, when Nagano et al (37) applied Sanger sequencing-based approaches to examine fungal diversity, the mycobiota recovered from medical environments bore remarkable similarity to those now being detected in surfaces of the Kibo experimental module flown to the International Space Station, all of which are prime examples of a low-biomass environment (49). The Kibo module-associated dominant fungal community components included Alternaria, Aspergillus, Candida, Cladosporium, Penicillium, Trichoderma, and Malassezia (49).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the fungal biota in Kibo changed from soil-borne fungi to a human origin. It was concluded in 2009 that cleanliness in Kibo was equivalent to that in an ISO Class 7 clean room environment on the ground (45). …”
Section: Abundance Of Bacteria and Fungi In The Issmentioning
confidence: 99%